A Bibliometric Analysis of Nanocrystalline Cellulose Synthesis for Packaging Application Research Using VOSviewer - Gusnine Sari Maulidah; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
Nanocrystalline cellulose is a type of renewable nano material that has many beneficial properties and has applications in various fields, one of which is packaging. This study aims to present an analytical map of studies in the manufacture of nanocrystalline cellulose using VOSviewer software. Based on the keywords “synthesis nanocrystalline cellulose” and “packaging application”, there were 500 related articles published in the 2017-2021 range. The results of the analysis show that the number of research articles on nanocrytalline cellulose synthesis has increased significantly every year. This is due to the need for new environmentally friendly and biodegradable materials for packaging. This research is expected to be a reference for researchers in determining the research topic to be carried out